Bacteriocin production by Enterococcus faecalis VRE 1492 using different media at varying pH and temperatures - Tan, Julie D. (Annals of Tropical Research, 2001)
Bacteriocins arc natural proteinaceous bactericidal substances produced by certain strains of bacteria and act against some other strains of the same or closely related species. This study was conducted to increase the level of bacteriocin production by Enterococcus faecalis VRE 1492 using selected growth media. Results showed that bacteriocin production by Enterococcus faecalis VRE 1492 was increased at different growth media, initial pH and fermentation time. Maximum production of bacteriocin was observed using De Man Rugosa and Sharpe (MRS) medium with glucose. The activity of bacteriocin was greatly increased in MRS medium with glucose at initial pH of 7.50 and 8.50 after 8 to 20 hours of fermentation at 30°C. Progressive increase in cell count from 0 to 24 hours of fermentation did not necessarily favor an increase in bacteriocin activity. After 20 hours of fermentation, the activity of bacteriocin decreased. The production of proteolytic enzymes by the bacterium was believed to inactivate the bacteriocin.